Evaluation of chromium in red blood cells as an indicator of exposure to hexavalent chromium: An in vitro study. (25th July 2016) - Devoy, Jérôme; Géhin, Antoine; Müller, Samuel; Melczer, Mathieu; Remy, Aurélie; Antoine, Guillaume; Sponne, Isabelle
Graphical abstract: Highlights: Our in-vitro study evaluates the selectivity of RBC in accumulating Cr(VI). A monotonic relationship exists between Cr(VI) added to blood and the Cr in RBC. Various parameters were tested, with negligible effects found on the relationship. Cr in RBC may be a good biomarker of recent exposure to Cr(VI). Abstract: Chromium(VI) compounds are classified as carcinogenic to humans. Whereas chromium measurements in urine and whole blood (i.e., including plasma) are indicative of recent exposure, chromium in red blood cells (RBC) is attributable specifically to Cr(VI) exposure. Before recommending Cr in RBC as a biological indicator of Cr(VI) exposure, in-vitro studies must be undertaken to assess its reliability. The present study examines the relationship between the chromium added to a blood sample and that subsequently found in the RBC. After incubation of total blood with chromium, RBC were isolated, counted and their viability assessed. Direct analysis of chromium in RBC was conducted using Atomic Absorption Spectrometry. Hexavalent, but not trivalent Cr, was seen to accumulate in the RBC and we found a strong correlation between the Cr(VI) concentration added to a blood sample and the amount of Cr in RBC. This relationship appears to be independent of the chemical properties of the human blood samples (e.g., different blood donors or different reducing capacities). Even though in-vivo studies are still needed to integrate our understanding of Cr(VI) toxicokinetics, our findings reinforce the idea that a single determination of the chromium concentration in RBC would enable biomonitoring of critical cases of Cr(VI) exposure.